Discharge Destination After Shoulder Arthroplasty: An Analysis of Discharge Outcomes, Placement Risk Factors, and Recent Trends. Issue 19 (1st October 2021) - Lavoie-Gagne, Ophelie; Lu, Yining; MacLean, Ian; Forlenza, Enrico; Forsythe, Brian
Abstract : Introduction: Rates of shoulder arthroplasty continue to increase. Factors influencing disposition and the effect discharge destination may have on perioperative outcomes are currently unknown. This study (1) investigates patients undergoing total shoulder arthroplasty subsequently discharged to home, skilled nursing facilities, and or independent rehabilitation facilities; (2) identifies differences in perioperative outcomes; and (3) investigates the risk of adverse events and readmission after nonhome disposition. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried for patients undergoing total shoulder arthroplasty from 2013 to 2018. Bivariate and multivariate analyses were conducted to determine the relationship between patient characteristics and risks of discharge to a non-home destination, discharge to an independent rehabilitation facility as opposed to a skilled nursing facility, severe postdischarge adverse events, and unplanned readmission. Results: Factors associated with discharge to a non-home facility included those older than 85 years of age (odds ratio [OR], 14.38), dialysis requirement (OR, 4.16), transfer from a non-home facility (OR, 3.69), dependent functional status (OR, 3.17), female sex (OR, 2.78), history of congestive heart failure (2.05), American Society of Anesthesiologists class >2 (OR, 1.97), longer length of stay (OR, 1.47), and body mass index >35 (OR, 1.29) ( P < 0.05). Patients discharged to a non-home facility had an approximately quadrupled rate of both major adverse events (8.6% vs 2.4%, P < 0.001) and minor adverse events (6.1% vs 1.4%, P < 0.001). Discharge to a non-home facility had a higher likelihood of a severe adverse event (OR, 1.82, P = 0.029) or unplanned readmission (OR, 1.60, P = 0.001). Conclusions: Non-home discharge destination demonstrated a notable negative impact on postoperative outcomes independent of medical complexity. Preoperative management of modifiable risk factors may decrease length of inpatient stay, rates of disposition to non-home facilities, and total cost of care. The benefit of more intense postoperative management at a non-home discharge destination must be carefully weighed against the independent risk of postoperative adverse events and readmissions.